The Visiting Medical Student Clerkship Program at Mayo Clinic - Mueller, Paul S. (Mayo Foundation for Medical Education and Research, 2010)
OBJECTIVE: To describe the history, objectives, statistics, and initiatives used to address challenges associated with the Mayo Clinic Visiting Medical Student (VMS) Clerkship Program. MATERIALS AND METHODS: Mayo Clinic administrative records were reviewed for calendar years 1995 through 2008 to determine the effect of interventions to increase the numbers of appropriately qualified international VMSs and underrepresented minority VMSs. For numerical data, descriptive statistics were used; for comparisons, χ(2) tests were performed. RESULTS: During the specified period, 4908 VMSs participated in the Mayo VMS Program (yearly mean [SD], 351 [24]). Most students were from US medical schools (3247 [66%]) and were male (3084 [63%]). Overall, 3101 VMSs (63%) applied for and 935 (30%) were appointed to Mayo Clinic residency program positions. Interventions to address the challenge of large numbers of international students who participated in our VMS program but did not apply for Mayo residency positions resulted in significantly fewer international students participating in our VMS program (P<.001), applying for Mayo residency program positions (P<.001), and being appointed to residency positions (P=.001). Interventions to address the challenge of low numbers of underrepresented minority students resulted in significantly more of these students participating in our VMS program (P=.005), applying for Mayo residency positions (P=.008), and being appointed to residency positions (P=.04). CONCLUSION: Our findings suggest that specific interventions can affect the characteristics of students who participate in VMS programs and who apply for and are appointed to residency program positions.